ON THE TRACES OF RELIGIOUS AT UFMG: SOME NOTES AND BRIEF REMINISCENCES - Perez, Léa Freitas (Debates do NER, 2007)
Teaching and research on religion is an established field of studies in the Sociology and Anthropology Department at the Federal University of Minas Gerais’ Philosophy and Human Sdences College. The text pursues, in the thickness of history, certain moments and events which have framed it.